Auditory Phonetic Analysis of Intonation Patterns in English Interrogative Sentences by Fourth-Semester English Literature Students at UIN Sunan Gunung Djati Bandung - Salma Ainnur Rahmah; Otong Setiawan Djuharie; Andang Saehu (INDO PUBLISHING, 2026)
This study examines the intonation patterns of English Wh-question sentences produced by fourth-semester English Literature students at UIN Sunan Gunung Djati Bandung, with a focus on the realization of suprasegmental features in spontaneous speech. A descriptive qualitative method with an auditory phonetic analysis framework was employed, where data were collected from 10 participants through spontaneous speaking activities using English and Indonesian prompts, and all responses were recorded for analysis. The results show three main intonation patterns: falling, rising, and flat. Falling intonation appears in some participants who demonstrate better control of English pronunciation, while rising and flat patterns are more dominant due to the influence of Indonesian intonation patterns and frequent code-mixing in speech. Overall, the findings indicate that students’ mastery of English intonation is still inconsistent in spontaneous communication, highlighting the need for more focused practice on suprasegmental aspects in English speaking instruction..